2022
DOI: 10.1177/21925682211069933
|View full text |Cite
|
Sign up to set email alerts
|

How Are Patients Reviewing Spine Surgeons Online? A Sentiment Analysis of Physician Review Website Written Comments

Abstract: Study Design A Sentiment Analysis of online reviews of spine surgeons. Objectives Physician review websites have significant impact on a patient’s provider selection. Written reviews are subjective, but sentiment analysis through machine learning can quantitatively analyze these reviews. This study analyzes online written reviews of spine surgeons and reports biases associated with demographic factors and trends in words utilized. Methods Online written and star-reviews of spine surgeons were obtained from hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Age analysis determined that younger ophthalmologists received higher star ratings and sentiment analysis scores than older ophthalmologists, a fnding that was in accordance with those of Smith et al [11]. Tis trend does not appear to be unique to the feld of ophthalmology, as Tang et al found similar results among reviews of hand and spine surgeons [14,15]. However, the geographic location of practice did not yield any statistically signifcant diferences with respect to star ratings or sentiment analysis scores.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Age analysis determined that younger ophthalmologists received higher star ratings and sentiment analysis scores than older ophthalmologists, a fnding that was in accordance with those of Smith et al [11]. Tis trend does not appear to be unique to the feld of ophthalmology, as Tang et al found similar results among reviews of hand and spine surgeons [14,15]. However, the geographic location of practice did not yield any statistically signifcant diferences with respect to star ratings or sentiment analysis scores.…”
Section: Discussionsupporting
confidence: 68%
“…Te R-squared value of this model was also used to optimize the minimum number of reviews required per physician to be included in this study. Tis method in determining the exclusion criteria was also used in the studies by Tang et al [14][15][16]. Te Student's t-tests were used to evaluate relationships between gender and both sentiment analysis scores and star ratings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly Crocamo et al found that the average VADER sentiment scores of tweets about COVID‐19 was negative, and ranged from −0.05 to −0.16 in early 2020 21 . Lastly, Tang et al found that the average sentiment score for reviews of male and female spine surgeons was 0.44 and 0.35, respectively 22 …”
Section: Discussionmentioning
confidence: 94%
“…21 Lastly, Tang et al found that the average sentiment score for reviews of male and female spine surgeons was 0.44 and 0.35, respectively. 22 Patient experience with CI's constituted significant proportions of both the "liked" (15.0%) and "negative" cohorts (9.4%). Patients described frustration with coordinating healthcare, pain associated with the implants, postsurgical facial nerve apraxia, malfunctioning of the implants, and difficulty coping with hearing loss/quality.…”
Section: Discussionmentioning
confidence: 99%